Gambaran Kepuasan Pelanggan pada Pelayanan Kesehatan Rawat Jalan - Derry Trisna Wahyuni Sukandar; Addies Adelia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Abstrack Quality service is a key factor in creating customer satisfaction and long-term loyalty. This study aims to evaluate customer satisfaction with service quality using the SERVQUAL method, which includes five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The research was conducted using a quantitative approach through the distribution of questionnaires to 50 respondents, with the results analyzed descriptively and presented in the form of graphs and percentages. In the Tangibles dimension, the majority of respondents rated the service at levels 3 and 4; 10% (5 people) were dissatisfied, 20% (10 people) were fairly satisfied, 18% (9 people) were satisfied, and 7% (14 people) were very satisfied. In the Empathy dimension, 6% (3 people) were dissatisfied, 26% (13 people) were fairly satisfied, 20% (10 people) were satisfied, and 10% (5 people) were very satisfied. For the Reliability dimension, 8% (4 people) were dissatisfied, 24% (12 people) were fairly satisfied, 18% (8 people) were satisfied, and 14% (7 people) were very satisfied. In the Responsiveness dimension, 4% (2 people) were very dissatisfied, 12% (6 people) dissatisfied, 26% (13 people) fairly satisfied, 14% (7 people) satisfied, and 6% (3 people) very satisfied. Meanwhile, in the Assurance dimension, 10% (5 people) were dissatisfied, 28% (14 people) fairly satisfied, 16% (8 people) satisfied, and 8% (4 people) very satisfied. The research method used is descriptive quantitative, with data collection carried out through closed-ended questionnaires measured using a Likert scale. The data were analyzed to identify patterns of customer satisfaction in each service dimension.The results indicate that customer satisfaction tends to fall into the fairly satisfied category, particularly in the dimensions of Tangibles, Empathy, and Reliability. However, the Responsiveness and Assurance dimensions show relatively lower proportions of high satisfaction, with a number of respondents expressing dissatisfaction. This indicates the need for improvement in staff responsiveness and their ability to provide trustworthy service. The conclusion of this study is that overall service quality is rated as fairly satisfying, but not yet optimal. There are opportunities for improvement, especially in dimensions related to direct customer interaction and trust. The study recommends enhancing staff training, particularly in responsiveness and interpersonal communication, improving response speed to customer requests, and conducting regular evaluations of service standards to ensure consistency and service reliability.